Bloodstream infections with rapidly growing nontuberculous mycobacteria. (December 2021) - Comba, Isin Yagmur; Tabaja, Hussam; Almeida, Natalia E. Castillo; Fida, Madiha; Saleh, Omar Abu
Abstract: Background: Bloodstream infections (BSI) with rapidly growing mycobacteria (RGM) resulted in recent nosocomial outbreaks predominantly in immunocompromised patients. A little is known about the clinical implications of RGM BSI with different species. Methods: We conducted a multicenter retrospective cohort study of patients with RGM BSI from November 2011 to December 2020. Demographic data, clinical presentation, laboratory and radiographic findings and microbiological characteristics were used to tabulate descriptive statistics. We performed a comparative analysis of patients with BSI due to Mycobacterium abscessus complex (MABC) vs. other RGM. Results: We identified 32 patients with positive blood cultures for RGM, 4/32 (12.5%) were considered to have unclear significance. The most common source for RGM BSI was intravascular catheters (14/28, 50%). Compared to other sources, patients with catheter-related bloodstream infection (CRBSI) received a shorter course of antimicrobial therapy (median [IQR]: one month [0.37–2.25] vs. six months [2–12]), ( P  = 0.01). The most common species isolated were MABC (12/28, 42.9%), followed by Mycobacterium fortuitum group (6/28, 21.4%) and Mycobacterium chelonae (6/28, 21.4%). Compared to other RGM, MABC BSI was more likely to be secondary to skin and soft tissue infection, associated with longer hospital stay ( P  = 0.04) and higher death rates despite a higher number of antimicrobial agents used for empirical and directed therapy per patient. Conclusion: MABC BSI is associated with an overall more resistant profile, longer hospital stay, and higher death rate despite a more aggressive therapy approach.